Про культурно-етнографічні спільності на півдні України в мезоліті: їх генезис та участь у неолітизації регіону - Телегін, Д.Я. (Археологія, 1999)
У статті обґрунтовується наявність трьох основних ліній культурно-історичного розвитку населення Азово-Чорноморського регіону в мезолітичну епоху: кримсько-білоліської, рогалицько-гребениківської та кукрекської. На підставі аналізу матеріалів автор намагається простежити зародження цих спільностей в пізньому палеоліті і їх роль у формуванні культур неоліту. На основании анализа кремневого инвентаря мезолитического времени в Азово-Причерноморском регионе Украины и смежных территорий выделяется три основные культурно-этнографические группы памятников, в том числе — крымско-белолесская с сегментами и классическими образцами пластин-анкошей, рогаликско-гребениковская с трапециями без сегментов и кукрекская с вкладышами и резцами кукрекского типа. Они сложились на различной генетической подоснове. Неодинакова была их роль в процессе неолитизации юга Украины.
Генетические корни сложения памятников крымско-белолесской группы с сегментами идут вглубь позднепалеолитического времени Крыма и Поднестровья.
Автохтонными по происхождению были и памятники рогаликско-гребениковской и кукрекской групп. Есть основания утверждать, что первая из них вырастает непосредственно из финальнопалеолитических памятников типа Осокоровки, Любимовки и др. на Днепре, где впервые появляются трапеции и другие кремневые изделия, которые потом бытуют в мезолите. В дальнейшем позднемезолитические комплексы Поднепровья стали одной из составных частей возникновения памятников днепро-донецкой неолитической культуры. Что же касается кукрекской генетической линии, то специалисты намечают примерно такую цепочку памятников на Южном Буге, непосредственно перерастающих один в другой. Дальнейший путь генетических преобразований мезолитических культур кукрекской линии развития (Игрень), ведет нас к сурской неолитической культуре. Analysis of Mesolithic flint tools from the Azov/Black Sea Region of Ukraine and neighbors territories captures the possibility to differentiate three main cultural and ethnic groups of sites: the Crimean-Bilolissia Group that can be described in terms of its segments and classical samples of the blades (ankosh); Rogalik-Grebennyki Group in terms of its trapezes (and without the segments); and the Kukrek Group in terms of its insets and burins of the Kukrek type. The groups varied territorially. Moreover, they distinguished each other by a number of features. They traced their origin to the different generic substrata. Their roles in the Neolithic processes in Southern Ukraine were also different.
Generic roots of the Crimean-Bilolissia Group traced back to the Later Paleolithic Period in Crimea and the Dniester River Region where the stations with the segments were investigated (Syuren 1, Korpach, and related sites).
The sites of the Rogalik-Grebennyki Group and the Kukrek Group were autochthonic in their origins. There are grounds for believing that the former emerged directly from such Final Paleolithic sites as Osokorki, Lyubimovka, and related sites of the Dnieper River Region, where the first trapezes and other flint tools had been produced and then widely used in the Mesolithic Period. The Later Mesolithic complexes from the Dnieper Region shaped the Dnieper and Donets Neolithic Culture. As for the Kukrek generic line, the researchers outline the following chain of sites in the South Bog Region: Sagaidak 1 — Anetovka — Abuzova Balka and related sites. Sagaidak 1 is dated from the Later Paleolithic Period (more than 20 thousand years ago, according to radiocarbon methodology), and Abuzova Balka is dated from the Developed Mesolithic Period. The path of generic transformation of the Mesolithic cultures of the Kukrek line (Igren) led to the Surskaya Neolithic Culture (Sursky, Shulaev, and related sites).